Double Jeopardy Upon Resumé Screening: When Achmed Is Less Employable Than Aïsha. Issue 3 (22nd July 2014) - Derous, Eva; Ryan, Ann Marie; Serlie, Alec W.
<x xml:space="preserve">Abstract</x> Applicants belong to multiple categories (e.g., male, ethnic minority) and a complex set of factors affects category activation and inhibition when making hiring decisions. Two field experiments with recruiters who regularly engage in resumé screening showed that the role of multiple categories (applicants' ethnicity and sex) in discrimination depended on job type and prejudice. Specifically, in both low‐ and high‐demand (i.e., complex) jobs, Arab women were rated more favorably than Arab men, particularly when considering levels of client contact. Across both studies, recruiters high in explicit ethnic prejudice were discriminatory only when applicants' job qualifications fit the job position less, lending support for the attributional‐ambiguity effect. Implicit attitudes did not play a strong role. Our study findings point to the complex nature of multiple categorization effects in the hiring process. Implications are considered as to how to avert hiring discrimination during resumé screening.